Decarboxylation of Paraconic Acids by a Silver(I) Nitrate/Persulfate Combination: An Entry to β-Nitro- and β-Hydroxy γ-Butyrolactones - Phae-nok, Supasorn; Kuhakarn, Chutima; Leowanawat, Pawaret; Reutrakul, Vichai; Soorukram, Darunee (Synlett, 2022)
Decarboxylative transformations of paraconic acids, a class of γ-butyrolactones containing a carboxylic acid group at the β-position as their characteristic functionality, by using a combination of AgNO3/K2S2O8 were investigated. The dual function of AgNO3 as an initiator of the decarboxylation process and as a source of nitrogen dioxide radicals that react with aliphatic carboxylic substrates is reported for the first time. Starting from paraconic acids, β-nitro- and β-hydroxy γ-butyrolactones were obtained in good combined yields (41–85%) with moderate selectivity in a one-pot operation. The reactions were completed within an acceptable reaction time (two hours) under mild conditions that were tolerated by the γ-butyrolactone core. This study provides a direct and site-specific entry to β-nitro- and β-hydroxy γ-butyrolactones, which are important precursors in organic transformations.
Keywords: decarboxylation; nitration; alkanoic acids; butyrolactones; nitroalkanes; paraconic acids